2019
DOI: 10.1371/journal.pone.0212444
|View full text |Cite
|
Sign up to set email alerts
|

Structured reporting of prostate magnetic resonance imaging has the potential to improve interdisciplinary communication

Abstract: Background Effective interdisciplinary communication of imaging findings is vital for patient care, as referring physicians depend on the contained information for the decision-making and subsequent treatment. Traditional radiology reports contain non-structured free text and potentially tangled information in narrative language, which can hamper the information transfer and diminish the clarity of the report. Therefore, this study investigates whether newly developed structured reports (SRs) of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 19 publications
0
24
0
2
Order By: Relevance
“…Clinicians require not only diagnostic accuracy but also language clarity in radiology reports (9, 10), which is needed for standardization of the radiology report. Previous study (11) revealed that a structured prostate MRI report could improve interdisciplinary communication and help urologists evaluate the exact location of PCa lesions more accurately, which could provide more accurate assessment of PCa and facilitate treatment planning. The TNM staging system for PCa, initially introduced in 1992 (12), plays an essential role in accurately reflecting the total cancer burden, evaluating the extent of spread at the time of diagnosis, and stratifying patients into prognostic groups for appropriate treatment planning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinicians require not only diagnostic accuracy but also language clarity in radiology reports (9, 10), which is needed for standardization of the radiology report. Previous study (11) revealed that a structured prostate MRI report could improve interdisciplinary communication and help urologists evaluate the exact location of PCa lesions more accurately, which could provide more accurate assessment of PCa and facilitate treatment planning. The TNM staging system for PCa, initially introduced in 1992 (12), plays an essential role in accurately reflecting the total cancer burden, evaluating the extent of spread at the time of diagnosis, and stratifying patients into prognostic groups for appropriate treatment planning.…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians require not only diagnostic accuracy but also language clarity in radiology reports ( 9 10 ), which is needed for standardization of the radiology report. Previous study ( 11 ) revealed that a structured prostate MRI report could improve interdisciplinary communication and help urologists evaluate the exact location of PCa lesions more accurately, which could provide more accurate assessment of PCa and facilitate treatment planning.…”
Section: Discussionmentioning
confidence: 99%
“…Web browser-based reporting tools can be used to generate structured reports. Several authors have used a commercial online reporting solution that is primarily designed to generate structured reports containing semantic sentences using predefined text phrases from itemised point-and-click data entry [ 5 , 9 , 28 , 34 36 ]. Pinto dos Santos et al have developed an open-source reporting platform that is compliant with IHE Management of Radiology Report Templates profile and stores report information in an additional database aside from RIS to facilitate data analysis [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…for rectal cancer [1,3] or pancreatic cancer [1,4]. Regarding content and presence of key descriptors, superiority of structured reports over conventional reports has been demonstrated for both of these diseases [5][6][7][8] as well as for several other malignancies such as prostate cancer [9] and hepatocellular carcinoma [10,11]. Thus, the advantages of structured reporting for primary diagnosis and initial local staging are well recognised.…”
Section: Introductionmentioning
confidence: 99%
“…Structured reporting (SR) has been advocated for various diagnostic modalities in radiology as well as in otolaryngology and other specialties with impact on treatment decisions and interdisciplinary communication [19][20][21][22][23][24][25]. The main benefit, especially for residents in training, is the standardization of the content and terminology which is known to improve report quality and time efficiency when compared to conventional reporting (CR) [19][20][21].…”
Section: Introductionmentioning
confidence: 99%